N–C chelated tetraaryl-pyrazole based organoboranes: A new class of aggregation induced enhanced emission materials. (October 2022) - Sa, Shreenibasa; Sahoo, Ashutosh; Mukherjee, Susmita; Perumal, Ajay; Venkatasubbaiah, Krishnan
Abstract: Luminescent materials, especially aggregation induced emissive materials attract considerable attention owing to their potential applications in optoelectronic devices, cell imaging, fluorescent sensors and so on. Hence, new aggregation induced emissive materials are in high demand. Here, we report, a series of N, C-chelated B–N coordinated tetraaryl pyrazoles (TAP-B1 to TAP-B4 ). The cumulative effect of the rigid organization of the phenyl groups imparts aggregation induced emissive behaviour and the extended conjugation imposed by the B–N coordination makes them as attractive new aggregation induced molecules. Deep blue OLED with CIE of (0.15, 0.15) is fabricated using TAP-B4 exhibits reduced efficiency roll off and outstanding luminance of up to 8024 cd/m 2 and remarkable maximum EL efficiencies of 4.5 lm/W and 6.1 cd/A with the maximum external quantum efficiency of 4.8%. Graphical abstract: Image 1 Highlights: Four new tetraaryl-pyrazole based tetracoordinate N, C-chelated boron compounds have been synthesized. All four boron compounds showed aggregation induced enhanced emission. Deep blue OLED with CIE of (0.15, 0.15) is fabricated using TAP-B4 exhibits outstanding luminance of up to 8024 cd/m 2 .